Discursos sobre a Àfrica presentes na mídia brasileira - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
In the present research, my aim is to write a discourse analysis about Africa and Africans present in the Brazillian media. There is a stereotyped image in the representation that Brazillians have of the continent and of Africans, a notion that evolves around, hunger, misery, conflicts, diseases and wild animals. That is why, this paper aims, to analyse the representations in two means of communication, Folha de São Paulo and o Globo, during the 2010 World Cup and the outbreak of ebola in 2014.I understand that it is with/in language that representations are produced, and the media is one of the networks which forms opinions that possess great influence in the construction of knowledge. The metodological procedure was developed based on the Bakhtinian theoretical-methodological framework, that focuses in socio-historic contexts, discursive chains, thematic contents and the value tones of the signs Africa and Africans. As regards the autors used to susbtantiate this research, I resorted to Hall (1990, 2006), Silva (2000), Martino (2010), that talk about identities; Albuquerque and Filho (2006) to contextualize the history of Black people in Brazil, a fundamental aspect to locate the discurse chain. For the studies of Language, I utilize authors from the Circle of Bakhtin, Volóchinov (2010) and Bakhtin (1997). As a result, I was able to observe that the enunciations present in the two Newspapers during the 2010 World Cup in South Africa and the ebola outbreak in 2014 in Western Africa, contribute to the promotion of stereotypes about Africa, because the News reinforces the continent and africans mainly under negative aspects, compromising their representation and, consequently, the construction of identity of Africans in Brasil and also of Black Brazillains, because it difficults their identification with Africa and Africans.
Keywords: Identidades; Enunciados; Jornais; Copa da África; Ebola; Identities; Enunciations; Newspaper; African World Cup; Ebola; CNPQ::LINGUISTICA, LETRAS E ARTES